2020
DOI: 10.1021/acsami.0c00962
|View full text |Cite
|
Sign up to set email alerts
|

BaTiO3 Nanosheets and Caps Grown on TiO2 Nanorod Arrays as Thin-Film Catalysts for Piezocatalytic Applications

Abstract: Powder-form piezocatalysts suffer from poor recyclability and pose a potential threat of creating serious secondary pollution, which restrict their practical applications. Thin-film piezocatalysts, which not only exhibit good recyclability but also fully contact with solution, are believed to be one of the solutions to address these problems. In this work, the nanostructured BaTiO3 (BTO) thin films were fabricated by a facile hydrothermal method for their potential applications in piezocatalysis. The verticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 68 publications
(113 reference statements)
2
25
0
Order By: Relevance
“…It is reported that tert ‐butanol (TBA) is a free radical scavenger which consumes the ⋅OH radicals in solution. [ 33,39,42,61 ] After the addition of TBA, the piezocatalytic efficiency is dramatically reduced (Figure 4d). On the other hand, the ferrous ions (Fe 2+ ) can accelerate the generation of ⋅OH through the Fenton reaction, [ 11,62,63 ] thereby improving the piezocatalytic efficiency in our system (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that tert ‐butanol (TBA) is a free radical scavenger which consumes the ⋅OH radicals in solution. [ 33,39,42,61 ] After the addition of TBA, the piezocatalytic efficiency is dramatically reduced (Figure 4d). On the other hand, the ferrous ions (Fe 2+ ) can accelerate the generation of ⋅OH through the Fenton reaction, [ 11,62,63 ] thereby improving the piezocatalytic efficiency in our system (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
“…Upon ultrasonic treatment, bubbles emerge in the solution and collapse, which can inflict a high pressure (≈10 8 Pa) and further generate piezoelectric dipoles (electrons, e − , and holes, h + ) on the foam surface. [ 33,39,42,61 ] As the energy level of the conduction band is −0.83 V (vs the normal hydrogen electrode, NHE) for BaTiO 3 , the piezoelectric electrons are able to reduce the dissolved O 2 to ⋅O 2 − (with a standard redox potential of −0.33 V vs NHE). On the other hand, the energy level for the valence band is 2.31 V versus NHE, by which the piezoelectric holes are capable of oxidizing OH − to ⋅OH (with a standard redox potential of 1.9 V vs NHE) in solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Over the past few years, typical piezoelectric nanomaterials have been exploited, including ZnO, Bi 4 Ti 3 O 12 , BaTiO 3 , Bi 0.5 Na 0.5 TiO 3 , C 3 N 4 , BN, WS 2 , and MoS 2 . [2][3][4][5][6][7][8][9][10] Among these materials, two-dimensional (2D) transition metal dichalcogenides (TMDs) have demonstrated excellent piezocatalytic performance in water splitting, contaminant degradation, carbon dioxide reduction, polymerization reaction and disease treatment due to their large piezoelectric coefficients, inherent layered crystal structures and high mechanical flexibility (that can withstand large strain). 11 However, their insufficient active sites and poor electrical conductivity hinder the improvement of their piezocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%